2017
DOI: 10.1016/j.nano.2017.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Real-time liver uptake and biodistribution of magnetic nanoparticles determined by AC biosusceptometry

Abstract: We describe the development of a joint in vivo/ex vivo protocol to monitor magnetic nanoparticles in animal models. Alternating current biosusceptometry (ACB) enables the assessment of magnetic nanoparticle accumulation, followed by quantitative analysis of concentrations in organs of interest. We present a study of real-time liver accumulation, followed by the assessment of sequential biodistribution using the same technique. For quantification, we validated our results by comparing all of the data with elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 55 publications
3
30
0
1
Order By: Relevance
“…In conclusion, intravenous administration of RITClabeled MNPSNPs (420 µg per animal) does not seem to affect mouse physiology although temporary accumulation in different organs occurs. The combination of silica shell, PEG and size led to similar distribution as published for other nanoparticles [43,44,60,[63][64][65]. The PEGylation in order to prolong the half-life period in the blood and to avoid the observed capture in inner organs by the MPS [74] was therefore not adequate enough [75,76].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In conclusion, intravenous administration of RITClabeled MNPSNPs (420 µg per animal) does not seem to affect mouse physiology although temporary accumulation in different organs occurs. The combination of silica shell, PEG and size led to similar distribution as published for other nanoparticles [43,44,60,[63][64][65]. The PEGylation in order to prolong the half-life period in the blood and to avoid the observed capture in inner organs by the MPS [74] was therefore not adequate enough [75,76].…”
Section: Discussionmentioning
confidence: 85%
“…In contrast to the lung, accumulation of MNPSNPs in the liver and in the red pulp of the spleen can be attributed to a passive particle accumulation due to higher permeability of sinusoidal capillaries (100-1000 nm pore size [61,62]) additional to active phagocytosis of macrophages [63]. Estevanato et al showed that already one hour after intravenous administration Kupffer cells were actively involved in capture of dextran functionalized magnetite nanoparticles (approx.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 Magnetic nanoparticles (MNPs) have several applications in nanomedicine such as contrast agents in magnetic resonance imaging (MRI), magnetic tracers in magnetic particle imaging (MPI) and alternating current biosusceptometry (ACB), and in magnetic hyperthermia therapy. [7][8][9][10] For a long time, nanoparticles (NPs) were only considered to be delivery systems in vaccines; however, there is now evidence showing that NPs can act as vaccine adjuvants with immunostimulatory capabilities. 11 Nonetheless, the use of metallic NPs in vaccinology is rare, and many effects and mechanisms of NPs have yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic measurements were made in triplicate and showed smaller variations than 0.5 millivolts (mV). After 3 measurements using the same chow, the average signal intensity value was determined and adopted to calculate the percentage of ferrite elimination in feces. BALB/c (n = 12) and C57BL/6 (n = 11) mice fasted for 12 hours prior to the experiments.…”
Section: Methodsmentioning
confidence: 99%